Soccer skill development in professionals - Huijgen, B. C. H.; Elferink-Gemser, M. T.; Post, W. J.; Visscher, C. (International Journal of Sports Medicine, 2009)
The purpose of this study was to investigate the relationship between the development of the technical skill dribbling during ages 14-18 and adulthood playing level. The results gained insight in the required level of the technical skill dribbling during adolescence to be capable of becoming a professional soccer player. Talented players (n=131), aged 14-18 were measured while they were part of a developmental soccer program, testing took place annually. The players were identified as professional (n=54) or amateur (n=77) later on in their career (age>20). In total 238 measurements of dribbling performance were assessed by means of the Shuttle Dribble Test. A longitudinal model estimated the development for optimal dribbling performance (peak dribbling) and for dribbling performance under fatigue (repeated dribbling), for players ultimately reaching professional status and for players reaching amateur status. The longitudinal results showed that during adolescence the talented players who ultimately became professionals were on average 0.3 s faster on 30m peak dribbling performance and on average 1 second faster on 3×30m repeated dribbling performance than the players who ultimately turned amateur (p=0.001). It is concluded that during adolescence dribbling performance can assist in identifying the best players for the future.